2020
DOI: 10.1111/1911-3846.12629
|View full text |Cite
|
Sign up to set email alerts
|

Do Auditors Accurately Predict Litigation and Reputation Consequences of Inaccurate Accounting Estimates?

Abstract: To effectively manage audit risk, auditors must correctly predict the potential litigation and reputation consequences associated with inaccurate accounting estimates. Accurate predictions are critical because underestimation of negative consequences leads to excess legal exposure and overestimation leads to overauditing. Our paper examines whether auditors correctly anticipate these litigation and reputation outcomes. We provide manager‐ and partner‐level auditors with case facts from an auditor negligence la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
3
1
Order By: Relevance
“…Unlike those two studies, Gimbar and Mercer (2021) found that auditors' judgments are more conservative than the desirable level inferred from actual court decisions for alleged misstatement trials. A higher threshold level is hinted by the study.…”
Section: Threshold Probability Levelcontrasting
confidence: 75%
See 1 more Smart Citation
“…Unlike those two studies, Gimbar and Mercer (2021) found that auditors' judgments are more conservative than the desirable level inferred from actual court decisions for alleged misstatement trials. A higher threshold level is hinted by the study.…”
Section: Threshold Probability Levelcontrasting
confidence: 75%
“…An incorrect probability assessment may cause auditing to be either inefficient or risky (Kinney, 1987;Gimbar & Mercer, 2021). Consequently, the manner that auditors use information when making probability judgments is of interest and importance.…”
Section: Judgments and Biases In Analytical Reviewmentioning
confidence: 99%
“…This is particularly important in the auditing context, where an audit firm as the seller of a service, the quality of which is often at times difficult to observe (Rothenberg, 2020, p. 371), to the extent that stakeholders are likely to directly associate the quality of the audit work with the reputation of the audit firm. In other words, given reputation is an important asset for an audit firm (Barton, 2005;Gimbar & Mercer, 2021;Hennes et al, 2014;Rothenberg, 2020), it serves as a salient cue that the work the audit firm performs is of high audit quality. Moreover, research has shown that a reputable firm attracts more clients (Skinner & Srinivasan, 2012;Weber et al, 2008) and is able to charge a higher audit fee (Ferguson et al, 2003;Francis et al, 2005), which supports the general perception that reputable firms perform higher quality audit work.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, due to this mismatch between the responsibility attributed and the responsibility the audit firm accepts, we expect that investors observing the interactions between the regulators and the audit firm will instead perceive the defensive actions as a cue that the audit firm has self-serving incentives to lessen the impact of the crisis (Ege et al, 2020;Martinow et al, 2020). 13 On this basis, we expect this will cause investors to view the audit firm's reputation negatively and to perceive inherent deficiencies in the audit process, leading to a lower perception of audit quality (Gimbar & Mercer, 2021;Rothenberg, 2020;Weber et al, 2008).…”
Section: Hypothesis Developmentmentioning
confidence: 99%